Avaliação da qualidade de vida do cirurgião plástico do estado de Goiás - Arruda, Fabiano Calixto Fortes de (2016)
Quality of life (QoL) is the result of the individual's perception of their position in life, in the context of the culture and in the value system in which they live and their relationship with their goals, expectations, standards and concerns. It is a well-studied subject in the health area, and in 2015 alone we obtained about 25,000 publications on the subject according to PUBMED data. In its current concept it relates factors such as: health, social relations, psychological and environmental aspects of the individual with their environment and with other individuals. Plastic surgery is a medical surgical specialty that developed mainly during the great world wars, thanks to the development of anesthesia and antibiotic therapy. The surgeons in this area develop activity in the aesthetic and reconstructive area. The purpose of this dissertatio n is to describe the quality of life of the plastic surgeon in the State of Goiás. This study is about a dissertation constructed in the form of a scientific article. The first article is an integrative review of published studies on the quality of life of the physician in Brazil. Medical related studies are still scarce and do not present the same instrument in the evaluation of professionals, but indicate that the worst domains of the WHOQOL instruments are related to the environment, social and psychological relations. The second article describes the sociodemographic and professional profile of the plastic surgeon in the state of Goiás. It presents a young population, predominantly male, with a time of activity in the area of less than 10 years, with about 2 children, working more than 40 hours a week and performing Aesthetic and reconstructive surgeries. When compared in relation to the time of action, it is observed that they increase the monthly income, the number of surgeries and decrease the weekly workload. The third article reports the results found on the quality of life of the plastic surgeon in the state of Goiás relating to variables present in the sociodemographic and professional profile. The study showed that surgeons who have children, are married, have a monthly income of more than R $ 30,000.00 (about 34 minimum wages), do not perform shifts or are performed in the specialty, work up to 40 hours a week and have more That 4 surgeries per week, present domains with better quality of life. It is concluded that the quality of life of the Goias’ plastic surgeon is influenced by factors such as marital status,professional working time, condition of association with the SBCP, no work shifts in another specialty, weekly workload and number of surgeries performed per week. Older surgeons have better quality of life. Therefore, it is necessary to create mechanisms that can cooperate with the new specialist so that he can adapt to the market and enjoy a better quality of life.